Factors influencing internal and external employability of employees - Juhdi, Nurita; Pa'wan, Fatimah; Othman, Noor Akmar; Mokhsin, Hanifah (Aston Journals, 2010)
The paper aimed at examining factors that influence employees’ employability. Factors that were examined are formal and informal career management practices, training, job experiences, education and tenure with current job. Employability is measured using two dimensions; internal and external employability. Data was collected using questionnaires that were distributed to selected organizations in various industries. Measurement items were adopted and adapted from previous studies. Two hundred and sixty employees participated in the study. Pearson correlation tests indicated that formal career management practices was positively related to external employability and internal employability. Informal career management practices were found only significantly related to external employability. The relationship with internal employability was insignificant. Training received by employees was both related to internal and external employability. On the other hand, job experiences were only significantly related to internal employability. Education and tenure were found only giving significant influence to external employability.